Cis-Acting Relaxases Guarantee Independent Mobilization of MOBQ4 Plasmids - Garcillán-Barcia, M. Pilar; Cuartas-Lanza, Raquel; Cuevas, Ana; de la Cruz, Fernando (Frontiers in Microbiology, 2019)
Plasmids are key vehicles of horizontal gene transfer and contribute greatly to bacterial genome plasticity. In this work, we studied a group of plasmids from enterobacteria that encode phylogenetically-related mobilization functions that populate the previously non-described MOBQ4 relaxase family. These plasmids encode two transfer genes: mobA coding for the MOBQ4 relaxase; and mobC, which is non-essential but enhances the plasmid mobilization frequency. The origin of transfer is located between these two divergently transcribed mob genes. We found that MPFI conjugative plasmids were the most efficient helpers for MOBQ4 conjugative dissemination among clinically-relevant enterobacteria. While highly similar in their mobilization module, two sub-groups with unrelated replicons (Rep_3 and ColE2) can be distinguished in this plasmid family. These subgroups can stably coexist (are compatible) and transfer independently, despite origin-of-transfer cross-recognition by their relaxases. Specific discrimination among their highly similar oriT sequences is guaranteed by the preferential cis activity of the MOBQ4 relaxases. Such a strategy would be biologically relevant in a scenario of co-residence of non-divergent elements to favor self-dissemination.